2015
DOI: 10.1590/0103-6440201300242
|View full text |Cite
|
Sign up to set email alerts
|

Does the Moment of Fiber Post Cutting Influence on the Retention to Root Dentin?

Abstract: Despite several advantages associated with pre-fabricated glass-fiber posts, the coronal portion of these posts must be cut to allow their use in various clinical situations. However, cutting the cemented post can generate stress on the bonding interface and affect the bond strength. The aim of this study was to investigate the effect the of fiber post cutting on the bond strength of root canals. Sixty bovine incisor roots were included in resin cylinders with simulated periodontal ligaments. Glass-fiber posts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(20 reference statements)
0
8
1
Order By: Relevance
“…To execute the case it was used the self-adhesive resin cement Rely X U200 (3M ESPE, Maplewood, Minnesota, USA) and the post was cut after luting. According to Borges et al [26], this protocol does not affect retention to root dentin when this type of luting agent is used.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To execute the case it was used the self-adhesive resin cement Rely X U200 (3M ESPE, Maplewood, Minnesota, USA) and the post was cut after luting. According to Borges et al [26], this protocol does not affect retention to root dentin when this type of luting agent is used.…”
Section: Discussionmentioning
confidence: 95%
“…To restore both teeth of these case reports it was used opaque, enamel and dentin composite resins by the stratification technique. A two-year study that evaluated nonvital bleached teeth and its composite resins restorations showed that the restorations presented excellent clinical performance [26].…”
Section: Discussionmentioning
confidence: 99%
“…A load was applied on the apical aspect of the root slice in the apical-coronal direction. The load was applied at a speed of 0.5 mm/min until failure, defined as the extrusion of the post segment from the root slice [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…As advantages have mechanical characteristics approaching to dentin, furthermore, the fiber posts have biocompatibility, mechanical strength and resistance to corrosion [ 2 , 3 ]. The use of this material reduces the probability of root fracture and reduces the time required to complete the restoration eliminating the laboratory procedures [ 4 , 5 ]. The retention of glass-fiber posts (GFPs) in the root canal depends on the quality of the hybrid layer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of the fiber glass reinforced posts has increased in recent years compared with the use of posts made of other materials, since the former offer a number of advantages: an elastic modulus similar to that of dentin, thereby allowing uniform distribution of tension along the longitudinal axis of the root (2); good esthetics in anterior sectors; and translucency allowing light transmission for correct polymerization of the bonding system (3,4)…”
Section: Introductionmentioning
confidence: 99%